The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.35808/ersj/1420
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Strategic Planning and Flexibility in Shaping SMEs Market Orientation in Turbulence Business Environment

Abstract: This study aims to investigate the impact of environmental turbulence, strategic planning and strategic flexibility toward market orientation. One hundred and eighty-six managers of Small and Medium Enterprises in Malang City, Indonesia were surveyed by using purposive sampling technique. Data was analysed by using Partial Least Squares. Internal environment has positive significant effects on both strategic planning and strategic flexibility. This study also found a significant effect of external environment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
(33 reference statements)
4
10
0
Order By: Relevance
“…These studies revealed that both entrepreneurial orientation and planning flexibility have positive effects on firm performance in different industries except oil and gas industry that was not considered among these past studies (See Arshad et al, 2014;Dibrel, Craig, & Neubaum, 2014;Gupta & Wales, 2017;Oladele & Olayiwola, 2018). Relatedly, Sumiati, Rofiq and Pramono (2019) and Mbengue and Ouakouak (2011) were in supported of the positive and significant findings among past studies that planning flexibility and entrepreneurial orientation positively and significantly affected firm performance. Both Sumiati et al (2019) and Mbengue and Ouakouak (2011) further asserted that external environment significantly affected firm overall performance in SMEs industry but they failed to investigate how external environmental factors affect both strategic entrepreneurship and firm performance in the oil and gas industry.…”
Section: Empirical Review and Hypotheses Developmentsupporting
confidence: 65%
“…These studies revealed that both entrepreneurial orientation and planning flexibility have positive effects on firm performance in different industries except oil and gas industry that was not considered among these past studies (See Arshad et al, 2014;Dibrel, Craig, & Neubaum, 2014;Gupta & Wales, 2017;Oladele & Olayiwola, 2018). Relatedly, Sumiati, Rofiq and Pramono (2019) and Mbengue and Ouakouak (2011) were in supported of the positive and significant findings among past studies that planning flexibility and entrepreneurial orientation positively and significantly affected firm performance. Both Sumiati et al (2019) and Mbengue and Ouakouak (2011) further asserted that external environment significantly affected firm overall performance in SMEs industry but they failed to investigate how external environmental factors affect both strategic entrepreneurship and firm performance in the oil and gas industry.…”
Section: Empirical Review and Hypotheses Developmentsupporting
confidence: 65%
“…Those two strategies are considered adequate for MSMEs to be applied. According to [26], strategy as planning plays an important role in mediating consumeroriented business performance. Determining the model (strategy) in business can significantly assist SMEs in making decisions…”
Section: Discussionmentioning
confidence: 99%
“…In the article [17] the author also describes the factors that can have consequences for entrepreneurs and emphasizes the structure of the economy and human capital, drawing attention to their role in the economic development of the state. Therefore, small business is becoming increasingly important in the economic development of the state [18] and, as noted in the article [19] they can be considered the main engine of economic growth because contribute to employment and changes in GDP (gross domestic product) by creating an intense competitive environment that requires strategic planning in a turbulent economic environment [20].…”
Section: Analysis Of Recent Researchmentioning
confidence: 99%